Immunotherapy for Lung Cancer: Has it Finally Arrived? - Mostafa, Ahmed A.; Morris, Don G. (Frontiers in Oncology, 2014)
The possible link between infection/inflammation/immune activation and a cancer patient’s outcome from both a causative and outcome point of view has long been postulated. Substantial progress in the understanding of tumour associated antigens/epitopes, immune cellular subpopulations, cytokine pathways/expression, the tumour microenvironment, and the balance between tumour immune suppression and stimulation have been made over the past decade. This knowledge has heralded a new era of tumor immunotherapy utilizing vaccines, immune checkpoint inhibition and oncolytic viruses. Despite significant progress in the molecular era now with targeted therapeutics such as EGFR tyrosine kinase inhibitors and ALK fusion protein inhibitors that have significantly improved the outcome of these specific lung cancer subpopulations, the overall 5 year survival for all non-small cell lung carcinoma (NSCLC) is still less than 20%. Unlike malignancies such as malignant melanoma, renal cell carcinoma and neuroblastoma given their documented spontaneous remission rates lung cancer historically has been felt to be resistant to immune approaches likely related to an immunosuppressive tumour microenvironment and/or lack of immune recognition. Defining responding populations, understanding the mechanism(s) underlying durable immune responses and the role of chemotherapy, radiation, oncolytic viruses and other tumour disrupting agents in augmenting immune responses have led to improved optimization of immune therapeutic strategies. The purpose of this mini review is to focus on the recent advances in lung immunotherapy with an emphasis on recent clinical trials in the last 5 years in NSCLC.